2012
DOI: 10.2139/ssrn.2089158
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Implicit Prejudice

Abstract: Implicit prejudices are social preferences that exist outside of conscious awareness or conscious control. In this review, we summarize evidence for three mechanisms that influence the expression of implicit prejudice: associative change, contextual change, and change in control over implicit prejudice. We then review the evidence (or lack thereof) for answers to five open issues in implicit prejudice reduction research: 1) what shows effectiveness in real-world application; 2) what doesn't work for implicit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 149 publications
1
42
0
Order By: Relevance
“…In particular, studies have shown that exposing adults to famous admired Black exemplars and disliked White exemplars reduces implicit pro‐White bias (Dasgupta & Greenwald, ; Joy‐Gaba & Nosek, ; Lai et al., ). The efficacy of this intervention among adults is believed to stem from a shift in the social context that places emphasis on individuals who contrast with usual stereotypes (Lai, Hoffman, & Nosek, ). As such, it has been suggested that this shift primes subtypes (e.g., “wealthy Black person”; “helpful Black person”) rather than leading adults to revise their prior beliefs about the larger groups (i.e., Black people).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies have shown that exposing adults to famous admired Black exemplars and disliked White exemplars reduces implicit pro‐White bias (Dasgupta & Greenwald, ; Joy‐Gaba & Nosek, ; Lai et al., ). The efficacy of this intervention among adults is believed to stem from a shift in the social context that places emphasis on individuals who contrast with usual stereotypes (Lai, Hoffman, & Nosek, ). As such, it has been suggested that this shift primes subtypes (e.g., “wealthy Black person”; “helpful Black person”) rather than leading adults to revise their prior beliefs about the larger groups (i.e., Black people).…”
Section: Discussionmentioning
confidence: 99%
“…One such factor is the prevalence of implicit, or unconscious, prejudice against out‐groups. Substantial work with adults points to the possibility that these implicit cognitions can be modified, but the magnitude of this change is quite small (for a review, see Lai, Hoffman & Nosek, ; Gawronski & Bodenhausen, ). For example, the average effect size of successful implicit bias change in a recent meta‐analysis examining the malleability of implicit biases in adults was d = .36 (Lai, Marini, Lehr, Cerruti, Shin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Most bias is subconscious and these pervasive, implicit biases even affect the actions of individuals who are not overtly biased (Lai et al, 2013; Staats et al, 2016). Our actions are also strongly affected by social prestige mechanisms that encompass non-meritocratic factors such as the wealth, reputation and selectivity of institutions (Bastedo & Bowman, 2010; Burris, 2004; Clauset et al, 2001).…”
Section: Discussionmentioning
confidence: 99%